Adverse Effect of Antithrombotic Medications on Bleeding Events and Comparison of Antithrombotic Agents in Hemodialysis Patients. Issue 1 (8th August 2018) - Daimon, Shoichiro
Abstract: Antithrombotic medications (AM) are mandatory for many hemodialysis patients, but the bleeding risk associated with this therapy is elevated. The frequency of bleeding events requiring discontinuation of AM, cessation of heparin use, and/or hospitalization was compared between hemodialysis patients with and without AM. All the hemodialysis patients in our clinic were investigated. AM were prescribed in 130 of 222 patients. Except for patients with cilostazol, those with AM had significantly more frequent bleeding events than those without AM ( P  < 0.01). Bleeding event frequency per 10 000 days of aspirin, clopidogrel, cilostazol, and warfarin prescription was 7.37, 5.95, 2.41, and 9.81, respectively, when restricted to administration of a single AM, which was 4.96, 2.87, 0.7, and 16.06, respectively. In patients without AM, it was 0.91. The bleeding risk associated with AM is elevated in hemodialysis patients and differs markedly depending on the agent used, with the lowest risk associated with cilostazol.